STAGES OF CREATING SOFTWARE FOR THE FORMATION OF PROFESSIONAL READINESS OF STUDENTS BASED ON AN INTEGRATIVE APPROACH (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Students are required to acquire certain knowledge, skills and competencies, as well as support them in various life situations. This goal can be achieved through integrated software applications, lessons, and extracurricular activities.